KOMUNIKASI HUKUM DALAM PERKARA PIDANA DAN PERDATA: KAJIAN PUSTAKA TENTANG KOMUNIKASI LISAN, TERTULIS, ELEKTRONIK, DAN DIGITAL SEBAGAI ALAT BUKTI - Anung Adityatjahja (Jurnal Komunikasi, 2026)
The rapid development of information and communication technology has significantly transformed legal communication systems in criminal and civil cases, particularly regarding the use of oral, written, electronic, and digital communication as legal evidence. This study aims to examine the evolution of legal communication in modern judicial systems through a literature review approach focusing on the validity, admissibility, and challenges of communication-based evidence in criminal and civil proceedings. This research employs a qualitative library research method by analyzing scientific articles, legal documents, regulations, and previous studies indexed in Scopus and published within the last five years. Data were collected through a literature review in academic databases and analyzed using content analysis and comparative analysis. The findings indicate that legal communication has shifted from conventional evidence systems toward digital and electronic evidence systems supported by technological advancements. Oral communication remains important through witness testimony and confessions; however, electronic and digital communications such as emails, instant messaging, social media, and audiovisual recordings increasingly dominate modern legal evidence practices. The study also reveals several major challenges, including digital authentication, data manipulation, privacy protection, cybersecurity, and chain of custody in digital evidence management. Furthermore, the emergence of artificial intelligence and deepfake technology has increased the complexity of verifying the authenticity of digital communication evidence in court proceedings. This study identifies a research gap in the limited integration of oral, written, electronic, and digital communication within a multidimensional legal evidence framework. The novelty of this research lies in its integrative perspective, combining legal studies, communication theory, and digital forensic approaches in understanding modern legal evidence systems. The study concludes that adaptive legal reform, standardized digital forensics, and enhanced digital literacy among law enforcement officers are essential to ensure legal certainty, transparency, and justice in the digital era.